Pengaruh Pemberian Terapi Progresive Muscle Relaxation Terhadap Stress Pasien Tuberculosis Paru - Riani, Suksi; Taslim, Muhammad Anis; Hikmah, Luluk (PT Karya Inovasi Berkelanjutan, 2025)
Introduction and Methods Tuberculosis is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis. Common clinical symptoms include coughing for more than two weeks, hemoptysis, shortness of breath, and other respiratory disorders. Additionally, tuberculosis patients may experience psychological disturbances such as anxiety, depression, hallucinations, stress, and irritability. Psychological conditions in patients experiencing stress require appropriate management to prevent further psychological complications. One of the therapeutic interventions that can be applied is Progressive Muscle Relaxation (PMR). This study employs a quantitative research method with a pre-experimental design, involving a total of 34 respondents. The research instrument used is the Perceived Stress Scale (PSS) questionnaire, which does not require validity and reliability testing as it is already standardized. Results The study results indicate that, prior to PMR therapy, the highest number of respondents (n=7) experienced severe stress. After receiving PMR therapy, only one respondent remained in the severe stress category. Conclusion and Recommendations The results of the Wilcoxon signed-rank test showed a p-value of 0.02, which is less than 0.05, indicating a significant effect of Progressive Muscle Relaxation (PMR) therapy on stress levels among pulmonary tuberculosis patients at Loekmono Hadi Kudus Regional Hospital. Based on these findings, it is recommended that nurses utilize PMR therapy as an independent nursing intervention to help reduce stress in pulmonary tuberculosis patients. Achievement of Sustainable Development Goals (SDGs) This study aims to test the hypothesis that Progressive Muscle Relaxation (PMR) can serve as a nursing intervention to manage stress in pulmonary tuberculosis patients. This research contributes to Sustainable Development Goal (SDG) 3: Ensuring Healthy Lives and Promoting Well-being for All at All Ages. Specifically, it aligns with Target 3.3, which aims to end the epidemics of AIDS, tuberculosis, malaria, and neglected tropical diseases, and combat hepatitis, waterborne diseases, and other communicable diseases by 2030.